Methylprednisolone in Pediatric Cardiac Surgery: Is There Enough Evidence? - van Saet, Annewil; Zeilmaker-Roest, Gerdien A.; Stolker, Robert J.; Bogers, Ad J. J. C.; Tibboel, Dick (Frontiers in Cardiovascular Medicine, 2021)
Corticosteroids have been used to decrease the inflammatory response to cardiac surgery and cardiopulmonary bypass in children for decades. Sparse information is present concerning the pharmacokinetics and pharmacodynamics of corticosteroids in the context of pediatric cardiac surgery. There is large interindividual variability in plasma concentrations, with indications for a larger volume of distribution in neonates compared to other age groups. There is ample evidence that perioperative use of MP leads to a decrease in pro-inflammatory mediators and an increase in anti-inflammatory mediators, with no difference in effect between doses of 2 and 30 mg/kg. No differences in inflammatory mediators have been shown between different times of administration relative to the start of surgery in various studies. MP has been shown to have a beneficial effect in certain subgroups of patients but is also associated with side effects. In lower risk categories, the balance between risk and benefit may be shifted toward risk. There is limited information on short- to medium-term outcome (mortality, low cardiac output syndrome, duration of mechanical ventilation, length of stay in the intensive care unit or the hospital), mostly from underpowered studies. No information on long-term outcome, such as neurodevelopmental outcome, is available. MP may provide a small benefit that is easily abolished by patient characteristics, surgical techniques, and perfusion management. The lack of evidence leads to large differences in practice between and within countries, and even within hospitals, so there is a need for adequately powered randomized studies.